Glycoside rich fraction from Spondias pinnata bark ameliorate iron overload induced oxidative stress and hepatic damage in Swiss albino mice. Issue 1 (December 2016) - Chaudhuri, Dipankar; Ghate, Nikhil; Panja, Sourav; Basu, Tapasree; Shendge, Anil; Mandal, Nripendranath
Abstract Background Iron in the overloaded condition in liver promotes the overproduction of free radicals that lead to oxidative stress and ultimately hepatic damage. The present study was designed to evaluate the ameliorating potential from iron overloaded hepatotoxicity by the glycosidic fraction fromSpondious pinnata bark (SPW1) along with its antioxidant property. Methods The fraction was tested for its in vitro antioxidant, free radical scavenging property and iron chelation potential via standard biochemical assays. Iron overload condition was generated by the intraperitoneal administration of iron dextran in mice. The levels of serum enzymes, antioxidant enzymes in liver, markers of hepatic damage, liver iron, and ferritin content were measured in response to the oral treatment of SPW1. Histopathology of the liver sections was performed for visual confirmation of the amelioration potential of SPW1. Results The fraction exhibited excellent in vitro antioxidant as well as free radical scavenging potential against both reactive oxygen species and reactive nitrogen species. Administration of SPW1 significantly normalized the disturbed levels of antioxidant enzymes, liver iron, lipid peroxidation, liver fibrosis, serum enzyme and ferritin better than standard desirox which were also supported by the morphological study of the liver sections. Phytochemical analysis as well as HPLC study, confirmed that the fraction mainly consisted of glycosidic phenolics and flavonoids that attributed to its biological activities. Conclusions The above results suggested that beneficial effects of SPW1 on iron overload induced hepatotoxicity that can be considered as a possible candidate against iron overload diseases.